2014
DOI: 10.15403/jgld.2014.1121.234.chcv
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of HCV Core Antigen Assay for the Management of Patients with Chronic Hepatitis C

Abstract: The Architect HCV core Ag assay might be an alternative for the diagnosis of active HCV infection if molecular tests are not available, and a useful method for the evaluation of sustained virological response in treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…During the window period of infection, anti‐HCV levels were undetected in two patients with positive HCV Ag, which confirmed that anti‐HCV detection is not sensitive in the window period of HCV infection . HCV Ag levels had a strong correlation with HCV RNA concentrations in patients with an active HCV infection, which was consistent with the previous reports, and Pearson's correlation coefficient was 0.891. The results of HCV Ag in two patients were in the gray zone (S/CO value: 0.82, 0.87) with HCV RNA level of 6600 and 6900 IU/mL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…During the window period of infection, anti‐HCV levels were undetected in two patients with positive HCV Ag, which confirmed that anti‐HCV detection is not sensitive in the window period of HCV infection . HCV Ag levels had a strong correlation with HCV RNA concentrations in patients with an active HCV infection, which was consistent with the previous reports, and Pearson's correlation coefficient was 0.891. The results of HCV Ag in two patients were in the gray zone (S/CO value: 0.82, 0.87) with HCV RNA level of 6600 and 6900 IU/mL.…”
Section: Discussionsupporting
confidence: 88%
“…HCV infections are a serious public health issue, with approximately 160‐170 million people infected worldwide, and early detection and treatment are key for preventing its transmission and providing effective treatment. Currently, anti‐HCV testing remains the preferred screening tool for HCV infections, but it is not sensitive during the window period of infections and hemodialysis; false positives are often observed in pregnancy and patients with autoimmune diseases, and it also cannot distinguish between active and past HCV infections . HCV RNA detection is used to confirm and manage antiviral therapy for HCV infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, genotype distribution was reported for 18 studies (Data Supplement Table 1) with genotype 1b being the most prevalent and genotypes 5 and 6 only minimally studied. In the univariate analysis, there were three outlier studies (25, 44, 45). In the Ergünay study from Turkey, HIV and HBV co-infection status were unknown and the genotype distribution was overall similar to other studies that reported data: 60.2% of participants had HCV genotype 1b infection, 2.2% genotype 1a, 0.8% genotypes 3 and 4, and 35.8% were unknown (Data Supplement Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, maintaining a low cutoff value partially counteracts the lack of sensitivity compared to HCV-RNA. According to the literature Laperche et al (2003), Krajden et al (2004), Valcavi et al (2004), Soffredini et al (2004), Chevaliez et al (2014), Florea et al (2014), the sensitivity of the technique decreases significantly in those samples with viral loads below 10 4 IU ml À1 , Therefore, it would be a mistake to consider negatives without retesting the samples with these results, since they can be either HCV-Ag negative or positive values associated with low viral load.…”
Section: Discussionmentioning
confidence: 99%